2007
DOI: 10.1080/00103620601094072
|View full text |Cite
|
Sign up to set email alerts
|

Polyaromatic Hydrocarbons in Rhizosphere Soil of Different Plants: Effect of Soil Properties, Plant Species, and Intensity of Anthropogenic Pressure

Abstract: The objective of the present study was to determine the content of polycyclic aromatic hydrocarbons (PAH) in the rhizospheres of some selected plant species (Cucumis dativus, Daucus carota, Allium cepa, Cueurbita, Petroselinum sativum, Cucurbitaceae, Phaseolus vulgaris, Beta vulgaris, Apium graveolens, Allium porrum, Vicia faba). Various anthropogenic influences on the PAH content in the rhizospheres of the three species selected were also studied. The PAH content was determined using the high performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Liste and Alexander (37) showed that rhizosphere of different plants is characterized by differentiate ability to PAHs degradation. This has also been confirmed by other authors (38,39). In the study presented, a perennial plant (willow) and annual plants were applied.…”
Section: Discussionsupporting
confidence: 80%
“…Liste and Alexander (37) showed that rhizosphere of different plants is characterized by differentiate ability to PAHs degradation. This has also been confirmed by other authors (38,39). In the study presented, a perennial plant (willow) and annual plants were applied.…”
Section: Discussionsupporting
confidence: 80%
“…7,8 Because of the complex symbiotic relationships between plant roots and their associated bacteria and mycorrhizal fungi, combined with the inherent physical difficulty involved in studying the rhizosphere, the reasons for enhanced contaminant loss in the rhizosphere are not completely understood. [1][2][3][4][5]9 Nevertheless, the performance and reliability of vegetated pollution control systems, such as phytoremediation, monitored natural attenuation, and stormwater bioretention cells, could be optimized through more efficient design if the fundamental mechanisms involved in the rhizosphere effect were better characterized.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The root-soil interface is complicated, and the fate of xenobiotic compounds in RS can be manipulated multifactorially. First, plant root exudates can activate the adhered compounds to pore water, and then enhance their transferability and bioavailability (Oleszczuk and Baran, 2007). Second, the degradation of xenobiotic compounds by indigenous microbes is improved, depending on the capacity of the contaminant degrader or plant promoting microbes to efficiently colonize growing roots (He et al, 2006;Gerhardt et al, 2009;Xia, 2012).…”
Section: Ratio Of Hfrs In Rs To Nrs Concentration Of Hfrs In Rs and Nmentioning
confidence: 99%